8 Acceleration time and ratio of acceleration time and ejection time in bicuspid aortic stenosis; a valid clinical measure?. (17th July 2020) - McSweeney, Jared; Dobson, Laura; Macnab, Anita
Abstract : Introduction: Evaluation of severity of aortic stenosis (AS) can be challenging due to discrepant Doppler and 2D data. Recent studies suggest that ejection dynamics, Acceleration Time (AT) and ratio of AT to Ejection Time (AT/ET), are useful measures in determining disease severity. However ejection dynamics have not been tested in patents with bicuspid aortic stenosis, where traditional Doppler indices have been shown to differ compared with patients with trileaflet (degenerative) aortic stenosis and where 2D valve planimetry has been shown to overestimate valve area. This study evaluates AT and AT/ET as grading parameters and examines their clinical validity. Methods: Echocardiograms from 200 patients (age 66±11yrs, 40% women) with moderate or severe AS were retrospectively identified and evaluated. 100 patients with moderate (n=50) or severe (n=50) bicuspid AS were matched for age, sex and stenosis grade with 100 patients with moderate (n=50) or severe (n=50) trileaflet AS. Ejection time (ET) was measured from the aortic valve CW Doppler as the time from onset to end of systolic flow. Acceleration time (AT) was defined as the time interval between the beginning of systolic flow and its peak velocity calculated from the aortic valve CW trace (figure 1 ). Results: Baseline and echocardiographic characteristics of the study population can be seen in tables 1 and 2 . In bicuspid AS, there was a significant difference between moderate and severe AS in ET (moderate 0.304 ± 0.029 vs severe 0.318 ± 0.031, p= 0.015), AT (moderate 0.099 ± 0.027 vs severe 0.126 ± 0.016, p=0.00) and AT/ET (moderate bicuspid 0.316 ± 0.026 vs severe bicuspid 0.396 ± 0.026, p=0.00). In trileaflet, differences in ET were not statistically significant (moderate 0.316 ± 0.029 vs severe 0.311 ± 0.023, p=0.334) but AT (moderate 0.096 ± 0.015 vs severe 0.117 ± 0.014, p=0.00) and AT/ET (moderate 0.302 ± 0.040 vs severe 0.376 ± 0.033, p=0.00) were both significantly different. Differences in AT/ET means were not statistically significant between moderate bicuspid and trileaflet groups (0.316±0.026, 0.302±0.040 p=0.052) but were between severe bicuspid and trileaflet groups (0.396±0.026, 0.376±0.033, p=0.011). AT and AT/ET showed strong correlation with aortic valve area (-0.651, -0.66), peak aortic velocity (-0.625, -0.629), mean pressure gradient (0.732, 0.712) where p<0.01. ROC analysis showed a cut off of 0.11 in AT distinguishes moderate and severe trileaflet AS (n=100) with an AUC of 0.88 with a sensitivity of 80% and a specificity of 90%. The same cut off in the bicuspid AS population (n=100) gave an AUC of 0.957 with a sensitivity of 90% and specificity of 92%. ROC analysis of AT/ET in trileaflet AS gave an AUC of 0.93. Using a cut off of 0.35, AT/ET had a sensitivity of 90% and specificity 88% for distinguishing between moderate and severe disease. ROC analysis of AT/ET in bicuspid AS gave an AUC of 0.96. The same cut off as above (0.35) gave specificity and sensitivity of 90%. Conclusion: AT and AT/ET are valid grading parameters for bicuspid and trileaflet AS. Both show better specificity and sensitivity differentiating moderate and severe AS in bicuspid than trileaflet valves. An AT/ET cut-off of 0.35 is clinically valid in both morphologies. Conflict of Interest: N/A